Whole Exome Sequencing Uncovers Germline Variants of Cancer-Related Genes in Sporadic Pheochromocytoma. (19th August 2018) - Urbini, Milena; Nannini, Margherita; Astolfi, Annalisa; Indio, Valentina; Vicennati, Valentina; De Luca, Matilde; Tarantino, Giuseppe; Corso, Federica; Saponara, Maristella; Gatto, Lidia; Santini, Donatella; Di Dalmazi, Guido; et al.
Abstract : Background . Pheochromocytomas (PCCs) show the highest degree of heritability in human neoplasms. However, despite the wide number of alterations until now reported in PCCs, it is likely that other susceptibility genes remain still unknown, especially for those PCCs not clearly syndromic. Methods . Whole exome sequencing of tumor DNA was performed on a set of twelve PCCs clinically defined as sporadic. Results . About 50% of PCCs examined had somatic mutations on the known susceptibility VHL, NF1, and RET genes. In addition to these driver events, mutations on SYNE1, ABCC10, and RAD54B genes were also detected. Moreover, extremely rare germline variants were present in half of the sporadic PCC samples analyzed, in particular variants of MAX and SAMD9L were detected in the germline of cases wild-type for mutations in the known susceptibility genes. Conclusions . Additional somatic passenger mutations can be associated with known susceptibility VHL, NF1, and RET genes in PCCs, and a wide number of germline variants with still unknown clinical significance can be detected in these patients. Therefore, many efforts should be aimed to better define the pathogenetic role of all these germline variants for discovering novel potential therapeutic targets for this disease still orphan of effective treatments.